Bhabinkamtibmas Performance in Visiting Activities to Prevent Fraud Crimes in the Jurisdiction of the Madiun City Police - Wisnu, Nila Cahyaning (Indonesian Journal of Police Studies, 2024)
The cases of fraud crimes within the jurisdiction of the Madiun City Police have increased over the past three years. These fraud crimes have resulted in material losses that impact the welfare of the community in the Madiun City Police jurisdiction. One of the most effective efforts needed to reduce cases of fraud is preemptive measures. Therefore, this research is necessary to determine the performance and management system implemented by the Bhabinkamtibmas during their visits in the Madiun City Police jurisdiction. A qualitative approach with descriptive analysis is used as the method for this research. Data collection was conducted through interviews, observations, and documentation. This research employs POAC management theory, SWOT analysis theory, and competency theory, accompanied by concepts of performance, Bhabinkamtibmas, visits, and fraud. Based on the research findings in the field, the performance of Bhabinkamtibmas in preventing fraud crimes within the jurisdiction of the Madiun City Police is still not optimal. This is marked by several internal and external factors that can affect the performance of Bhabinkamtibmas. Several factors hinder the implementation of outreach activities through visits, both from internal and external factors, such as the dual roles performed by Bhabinkamtibmas outside their primary functions and duties, and the lack of prepared materials on fraud crimes, leading Bhabinkamtibmas to only provide supplementary information. Externally, many modus operandi are used by perpetrators. Based on the above research findings, the author seeks solutions to the problems faced by Bhabinkamtibmas. It is recommended that in the planning stage, activities be carefully arranged, tasks be divided according to established regulations, and Bhabinkamtibmas engage more intensively in providing outreach regarding fraud crimes.